Emotionally and motivationally supportive classrooms: A state-trait analysis of lesson- and classroom-specific variation in teacher- and student-reported teacher enthusiasm and student engagement. (October 2021) - Gaspard, Hanna; Lauermann, Fani
Abstract: Teacher enthusiasm and student engagement are often interrelated and have important implications for student learning and students' and teachers' well-being. However, results on the lesson-specific variation of teachers' and students' affective-motivational experiences and their interplay are scarce. This study investigated variation in teacher enthusiasm and student engagement, each rated by teachers ( n  = 70) and students ( n  = 1537), as indicators of a shared affective-motivational climate in ninth-grade math classrooms across five consecutive lessons. Multitrait-multistate analyses revealed substantial "trait-like" consistency in all four affective-motivational measures. However, there was also a substantial degree of "state-like" lesson-specific variance that was shared across the four measures. This indicates that teachers' and students' affective-motivational experiences are shaped by situation-specific influences and person-by-context interactions, which are shared between teachers and students. Teacher gender, teaching experience, class-level achievement, and the availability of motivationally supportive instructional interventions failed to explain substantial variance in these associations. Highlights: Teacher enthusiasm and student engagement form a shared affective-motivational climate. The affective-motivational climate of a class includes trait-like and state-like components. Teacher enthusiasm and class-level student engagement showed trait-like consistency. Joint lesson-to-lesson fluctuations in teacher and student experiences were supported.